Aluminum-based carbon film photo-thermal evaporator and preparation method and application thereof
By forming a periodic tank-like structure on the aluminum-based carbon film photothermal evaporator and combining the characteristics of furfural carbon, the problem of deterioration of mechanical properties and light absorption performance of the interface solar evaporation system is solved, efficient photothermal conversion and evaporation rate are achieved, and the long-term stability and salt resistance performance of the system are ensured through the concentrated brine drainage mode.
Patent Information
- Application Number
- CN202411695708.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Under the influence of factors such as bad weather and seawater corrosion, the mechanical properties and light absorption performance of the interface solar evaporation system have deteriorated, making it difficult to operate stably and efficiently for a long time, and the salt deposition phenomenon seriously affects the service life.
Aluminum-based carbon film photothermal evaporator is used to form a periodic groove-like structure on the surface of the Al sheet through laser etching technology, optimize the distribution of photothermal conversion materials, and combine the photothermal conversion ability and hydrophilic properties of furfural carbon to design channels for water flow diffusion and steam emanation. At the same time, concentrated brine drainage mode is adopted to achieve salt resistance and long-term stable and efficient operation.
It significantly improves the photothermal conversion efficiency and evaporation rate, ensures that the system remains stable and efficient during long-term operation, extends its service life, and effectively solves the problem of salt deposition.
Smart Images

Figure CN119503938A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal materials, and in particular to an aluminum-based carbon film photothermal evaporator and a preparation method and application thereof. Background Art
[0002] With the rapid growth of population and the rapid development of industrialization, the shortage of fresh water resources has restricted the development of science and technology and threatened human survival. Interfacial solar evaporation (ISE) technology is a new generation of green, low-energy fresh water production technology. Compared with commercial reverse osmosis and multi-effect distillation technologies, it does not rely on the consumption of fossil energy, so it can be applied to remote mountainous areas. Although breakthrough progress has been achieved in evaporation rate and energy utilization efficiency through the preparation of photothermal materials, regulation of water transportation methods, and enhanced thermal management. Researchers have developed various types of evaporators such as carbon-based, hydrogel, aerogel, paper-based, textile-based and metal-based. Among them, metal-based evaporators have attracted the attention of researchers due to their advantages such as high thermal conductivity, strong mechanical properties, good durability, convenient transportation and scalable production.
[0003] As a new generation of seawater desalination technology with green, environmental protection and low energy consumption, interfacial solar-driven water evaporation technology is one of the important methods to deal with the increasingly serious freshwater crisis. However, due to the influence of bad weather and seawater corrosion, the mechanical properties and light absorption properties of the interfacial solar evaporation system deteriorate, making it difficult to achieve long-term stable and efficient operation during the long-term evaporation process. In addition, the salt deposition phenomenon during the evaporation process seriously endangers the service life of the photothermal absorber, thereby affecting the operation of the ISE system and making it difficult to achieve the expected production goals. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides an aluminum-based carbon film photothermal evaporator and a preparation method and application thereof. With L-Al as a substrate, a periodic groove structure is formed on the surface of the Al sheet by laser etching technology. This microscopic network structure not only optimizes the distribution of photothermal conversion materials, but also opens up channels for the effective diffusion of water flow and the rapid escape of steam through the design of the groove structure, and also provides a stable site for the attachment of furfural carbonization. Combined with the excellent photothermal conversion ability, hydrophilicity and evaporation enthalpy reduction mechanism of furfural carbon, the photothermal conversion efficiency and evaporation rate are significantly improved. By combining with the concentrated brine drainage mode, a high-performance interface solar evaporation system with excellent salt resistance and stable and efficient operation during long-term evaporation is obtained.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing an aluminum-based carbon film photothermal evaporator, the preparation method is as follows: Laser etching is performed on the surface of the Al sheet to obtain an Al sheet with a periodic groove structure on the surface, thereby obtaining product 1; Adding the furfural oxalic acid solution dropwise into the periodic groove-like structure on the surface of the product 1 until a uniform liquid film is formed on the periodic groove-like structure on the surface of the product 1, thereby obtaining the product 2; The product 2 is prepolymerized and carbonized to obtain the product 3; The hydrophilic sites of product 3 were activated to obtain an aluminum-based carbon film photothermal evaporator.
[0006] Further, laser etching is performed on the surface of the Al sheet to obtain an Al sheet having a periodic groove structure on the surface. In the step of obtaining product 1, specifically: The laser etching range is 2.5 cm×3.0 cm, the laser spot diameter is 0.05 mm, the laser focal length is 11.0 cm, the spacing between laser beams is 0.1 mm~0.2 mm, the laser beam scanning path is vertical scanning, and the etching path includes horizontal and vertical directions.
[0007] Further, laser etching is performed on the surface of the Al sheet to obtain an Al sheet having a periodic groove structure on the surface. In the step of obtaining product 1, specifically: The periodic groove structure is a square array composed of a plurality of square groove structures formed by the intersection of transverse and longitudinal etching paths.
[0008] Further, the furfural oxalic acid solution is dripped into the periodic groove structure on the surface of the product 1 until a uniform liquid film is formed on the periodic groove structure on the surface of the product 1 to obtain the step of product 2, specifically: The oxalic acid and furfural are mixed in a molar ratio of 0.01 to 0.011 to obtain a furfural oxalic acid solution.
[0009] Further, in the step of prepolymerizing and carbonizing the product 2 to obtain the product 3, specifically: The product 2 was dried at 90°C for 48 h for prepolymerization.
[0010] Further, in the step of prepolymerizing and carbonizing the product 2 to obtain the product 3, specifically: The prepolymerized product 2 is placed in a protective atmosphere and carbonized at a temperature of 500° C. to 800° C. to obtain a product 3.
[0011] Furthermore, the flow rate under the protective atmosphere does not exceed 50 sccm.
[0012] The present invention also provides an aluminum-based carbon film photothermal evaporator, which is prepared by the above preparation method.
[0013] The present invention also provides an ISE system, wherein the photothermal absorption layer adopts the above-mentioned aluminum-based carbon film photothermal evaporator.
[0014] Furthermore, based on the concentrated brine drainage mode, a water supply channel and a concentrated brine drainage channel are set on the aluminum-based carbon film photothermal evaporator, and both sides of the aluminum-based carbon film photothermal evaporator are in contact with the head of the water supply channel, and the tail of the water supply channel is in contact with water for supplying water to the aluminum-based carbon film photothermal evaporator; the two opposite outer sides of the water supply channel on the aluminum-based carbon film photothermal evaporator are in contact with the head of the concentrated brine drainage channel, and the tail of the concentrated brine drainage channel is connected to the concentrated brine recovery device.
[0015] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides an aluminum-based carbon film photothermal evaporator, which forms a periodic groove structure on the surface of the Al sheet through laser etching technology. This innovative design not only enhances the surface area of the material, but also provides a stable site for the attachment of furfural carbonization. This microscopic network structure not only optimizes the distribution of photothermal conversion materials, but also opens up channels for the effective diffusion of water flow and the rapid escape of steam through the design of the groove structure. This innovation in structural design has significantly improved the photothermal conversion efficiency and evaporation rate of the aluminum-based carbon film photothermal evaporator.
[0016] Furthermore, thanks to the excellent photothermal conversion capability of furfural carbon, the aluminum-based carbon film photothermal evaporator prepared by the present invention can efficiently convert light energy into heat energy under illumination conditions, thereby driving the evaporation of water. At the same time, the hydrophilicity of furfural carbon and the mechanism of reducing the evaporation enthalpy further enhance the evaporation performance of the evaporator. The experimental results show that under an illumination intensity of 1 sun, the evaporator can obtain up to 2.12 kg / m2 when desalinating 3.5 wt% simulated seawater. -2 h -1 The evaporation rate and energy efficiency of 91.8% make the present invention have broad application prospects in the fields of seawater desalination and sewage treatment.
[0017] The present invention also combines the concentrated brine drainage mode to obtain a high-performance interfacial solar evaporation system with excellent salt resistance and stable and efficient operation during long-term evaporation. This feature makes the present invention have a wider application potential in fields such as seawater desalination that require the treatment of high-salinity water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Surface morphologies of L-Al and C@L-AL prepared at different carbonization temperatures, including a) L-Al, b) C@L-Al-1, c) C@L-Al-2, and d) C@L-Al-3.
[0019] Figure 2Changes in mass loss of C@L-Al-2 desalinating seawater of different simulated concentrations.
[0020] Figure 3 is the evaporation rate and energy utilization efficiency.
[0021] Figure 4 The evaporation rate of 3.5wt% simulated seawater for 8h.
[0022] Figure 5 The evaporation rate of 3.5wt% simulated seawater for 15 cycles. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0024] Example 1 The present invention provides an aluminum-based carbon film photothermal evaporator, and the preparation method is as follows: (1) Al sheet preprocessing Place a 0.4 mm thick Al sheet (size 10 cm × 15 cm) on the non-woven fabric and first polish it with 2000 grit sandpaper to remove pollutants on the surface of the aluminum sheet. Then continue polishing with 400 grit sandpaper until it is flat and smooth. Then wipe it clean with alcohol cotton and blow it dry with nitrogen.
[0025] (2) Etching periodic groove structures on the surface of Al sheets The Al sheet polished and cleaned in step 1 was fixed on the workbench of the laser marking machine (LG20, HGLASER, China). The power was set to 20 W and the speed was set to 90 mm s. -1 , a laser beam with a frequency of 30 KHz is vertically irradiated on the cleaned Al sheet surface for laser etching. Among them, the laser beam etching range is 2.5 cm×3.0 cm, the laser spot diameter is 0.05 mm, and the laser focal length is 11.0 cm. The laser beam scanning path is vertical scanning. The spacing between the laser beams is adjusted to 0.15 mm to etch the Al sheet surface. The Al sheet after laser treatment is called L-AL.
[0026] (3) Polymerization of furfural on the surface of L-AL sheets with periodic groove structures 1) Mix oxalic acid and furfural, stir for 15 min in a dark environment to obtain a furfural oxalic acid solution, and then place it in a dark and cool place for use.
[0027] The molar ratio of oxalic acid to furfural is 0.01.
[0028] 2) The oxalic acid / furfuryl alcohol solution was slowly added dropwise onto the L-Al surface. The mixed solution diffused on the L-Al surface under the capillary action. The liquid film of the mixed solution added to the L-Al was uniform. The sample was then placed in an oven at 90 °C and dried for 48 h to prepolymerize furfural, thereby obtaining sample 1 with a brown-black surface.
[0029] 3) Place the above sample 1 in a crucible and perform carbonization treatment at 500°C in a nitrogen atmosphere with a flow rate of 20 sccm. After the temperature of the tube furnace drops to room temperature, take out the sample 2 with a black surface. After that, soak the carbonized sample 2 in deionized water for 72 hours to activate the hydrophilic sites. Finally, place the sample 2 in a 60°C forced air drying oven and dry it for 12 hours to obtain an aluminum-based carbon film photothermal evaporator, which is named C@L-Al-1.
[0030] Example 2 The present invention provides an aluminum-based carbon film photothermal evaporator, and the preparation method is as follows: (1) Al sheet preprocessing Place a 0.4 mm thick Al sheet (size 10 cm × 15 cm) on the non-woven fabric and first polish it with 2000 grit sandpaper to remove pollutants on the surface of the aluminum sheet. Then continue polishing with 400 grit sandpaper until it is flat and smooth. Then wipe it clean with alcohol cotton and blow it dry with nitrogen.
[0031] (2) Etching periodic groove structures on the surface of Al sheets The Al sheet polished and cleaned in step 1 was fixed on the workbench of the laser marking machine (LG20, HGLASER, China). The power was set to 20 W and the speed was set to 90 mm s. -1 , a laser beam with a frequency of 30 KHz is vertically irradiated on the cleaned Al sheet surface for laser etching. Among them, the laser beam etching range is 2.5 cm×3.0 cm, the laser spot diameter is 0.05 mm, and the laser focal length is 11.0 cm. The laser beam scanning path is vertical scanning. The spacing between the laser beams is adjusted to 0.15 mm to etch the Al sheet surface. The Al sheet after laser treatment is called L-AL.
[0032] (3) Polymerization of furfural on the surface of L-AL sheets with periodic groove structures 1) Mix oxalic acid and furfural, stir for 15 min in a dark environment to obtain a furfural oxalic acid solution, and then place it in a dark and cool place for use.
[0033] The molar ratio of oxalic acid to furfural is 0.01.
[0034] 2) The oxalic acid / furfuryl alcohol solution was slowly added dropwise onto the L-Al surface. The mixed solution diffused on the L-Al surface under the capillary action. The liquid film of the mixed solution added to the L-Al was uniform. The sample was then placed in an oven at 90 °C and dried for 48 h to prepolymerize furfural, thereby obtaining sample 1 with a brown-black surface.
[0035] 3) Place the above sample 1 in a crucible and perform carbonization treatment at 700°C in a nitrogen atmosphere with a flow rate of 20 sccm (not exceeding 50 sccm). After the temperature of the tube furnace drops to room temperature, take out the sample 2 with a black surface. After that, soak the carbonized sample 2 in deionized water for 72 hours to activate the hydrophilic sites. Finally, place the sample 2 in a 60°C forced air drying oven and dry it for 12 hours to obtain an aluminum-based carbon film photothermal evaporator, which is named C@L-Al-2.
[0036] Example 3 The present invention provides an aluminum-based carbon film photothermal evaporator, and the preparation method is as follows: (1) Al sheet preprocessing Place a 0.4 mm thick Al sheet (size 10 cm × 15 cm) on the non-woven fabric and first polish it with 2000 grit sandpaper to remove pollutants on the surface of the aluminum sheet. Then continue polishing with 400 grit sandpaper until it is flat and smooth. Then wipe it clean with alcohol cotton and blow it dry with nitrogen.
[0037] (2) Etching periodic groove structures on the surface of Al sheets The Al sheet polished and cleaned in step 1 was fixed on the workbench of the laser marking machine (LG20, HGLASER, China). The power was set to 20 W and the speed was set to 90 mm s. -1 , a laser beam with a frequency of 30 KHz is vertically irradiated on the cleaned Al sheet surface for laser etching. Among them, the laser beam etching range is 2.5 cm×3.0 cm, the laser spot diameter is 0.05 mm, and the laser focal length is 11.0 cm. The laser beam scanning path is vertical scanning. The spacing between the laser beams is adjusted to 0.15 mm to etch the Al sheet surface. The Al sheet after laser treatment is called L-AL.
[0038] (3) Polymerization of furfural on the surface of L-AL sheets with periodic groove structures 1) Mix oxalic acid and furfural, stir for 15 min in a dark environment to obtain a furfural oxalic acid solution, and then place it in a dark and cool place for use.
[0039] The molar ratio of oxalic acid to furfural is 0.01.
[0040] 2) The oxalic acid / furfuryl alcohol solution was slowly added dropwise onto the L-Al surface. The mixed solution diffused on the L-Al surface under the capillary action. The liquid film of the mixed solution added to the L-Al was uniform. The sample was then placed in an oven at 90 °C and dried for 48 h to prepolymerize furfural, thereby obtaining sample 1 with a brown-black surface.
[0041] 3) Place the above sample 1 in a crucible and perform carbonization treatment at 800°C in a nitrogen atmosphere with a flow rate of 20 sccm. After the temperature of the tube furnace drops to room temperature, take out the sample 2 with a black surface. After that, soak the carbonized sample 2 in deionized water for 72 hours to activate the hydrophilic sites. Finally, place the sample 2 in a 60°C forced air drying oven and dry it for 12 hours to obtain an aluminum-based carbon film photothermal evaporator, which is named C@L-Al-3.
[0042] Example 4 The present invention provides an aluminum-based carbon film photothermal evaporator, and the preparation method is as follows: (1) Al sheet preprocessing Place a 0.4 mm thick Al sheet (size 10 cm × 15 cm) on the non-woven fabric and first polish it with 2000 grit sandpaper to remove pollutants on the surface of the aluminum sheet. Then continue polishing with 400 grit sandpaper until it is flat and smooth. Then wipe it clean with alcohol cotton and blow it dry with nitrogen.
[0043] (2) Etching periodic groove structures on the surface of Al sheets The Al sheet polished smooth and clean in step 1 was fixed on the workbench of the laser marking machine (LG20, HGLASER, China). The power was set to 20 W and the speed was set to 90 mm s. -1 , a laser beam with a frequency of 30 KHz is vertically irradiated on the cleaned Al sheet surface for laser etching. Among them, the laser beam etching range is 2.5 cm×3.0 cm, the laser spot diameter is 0.05 mm, and the laser focal length is 11.0 cm. The laser beam scanning path is vertical scanning. The spacing between the laser beams is adjusted to 0.2 mm to etch the Al sheet surface. The Al sheet after laser treatment is called L-AL.
[0044] (3) Polymerization of furfural on the surface of L-AL sheets with periodic groove structures 1) Mix oxalic acid and furfural, stir for 15 min in a dark environment to obtain a furfural oxalic acid solution, and then place it in a dark and cool place for use.
[0045] The molar ratio of oxalic acid to furfural is 0.011.
[0046] 2) The oxalic acid / furfuryl alcohol solution was slowly added dropwise onto the L-Al surface. The mixed solution diffused on the L-Al surface under the capillary action. The liquid film of the mixed solution added to the L-Al was uniform. The sample was then placed in an oven at 90 °C and dried for 48 h to prepolymerize furfural, thereby obtaining sample 1 with a brown-black surface.
[0047] 3) Place the above sample 1 in a crucible and perform carbonization treatment at 600°C in an argon atmosphere with a flow rate of 30 sccm. After the temperature of the tube furnace drops to room temperature, take out the sample 2 with a black surface. After that, soak the carbonized sample 2 in deionized water for 72 hours to activate the hydrophilic sites. Finally, place the sample 2 in a 60°C forced air drying oven and dry it for 12 hours to obtain an aluminum-based carbon film photothermal evaporator, which is named C@L-Al-4.
[0048] Example 5 The present invention provides an aluminum-based carbon film photothermal evaporator, and the preparation method is as follows: (1) Al sheet preprocessing Place a 0.4 mm thick Al sheet (size 10 cm × 15 cm) on the non-woven fabric and first polish it with 2000 grit sandpaper to remove pollutants on the surface of the aluminum sheet. Then continue polishing with 400 grit sandpaper until it is flat and smooth. Then wipe it clean with alcohol cotton and blow it dry with nitrogen.
[0049] (2) Etching periodic groove structures on the surface of Al sheets The Al sheet polished smooth and clean in step 1 was fixed on the workbench of the laser marking machine (LG20, HGLASER, China). The power was set to 20 W and the speed was set to 90 mm s. -1 , a laser beam with a frequency of 30 KHz is vertically irradiated on the cleaned Al sheet surface for laser etching. Among them, the laser beam etching range is 2.5 cm×3.0 cm, the laser spot diameter is 0.05 mm, and the laser focal length is 11.0 cm. The laser beam scanning path is vertical scanning. The spacing between the laser beams is adjusted to 0.1 mm to etch the Al sheet surface. The Al sheet after laser treatment is called L-AL.
[0050] (3) Polymerization of furfural on the surface of L-AL sheets with periodic groove structures 1) Mix oxalic acid and furfural, stir for 15 min in a dark environment to obtain a furfural oxalic acid solution, and then place it in a dark and cool place for use.
[0051] The molar ratio of oxalic acid to furfural is 0.0105.
[0052] 2) The oxalic acid / furfuryl alcohol solution was slowly added dropwise onto the L-Al surface. The mixed solution diffused on the L-Al surface under the capillary action. The liquid film of the mixed solution added to the L-Al was uniform. The sample was then placed in an oven at 90 °C and dried for 48 h to prepolymerize furfural, thereby obtaining sample 1 with a brown-black surface.
[0053] 3) Place the above sample 1 in a crucible and perform carbonization treatment at 500°C, 700°C, and 800°C in an argon atmosphere with a flow rate of 50 sccm. After the temperature of the tube furnace drops to room temperature, take out the sample 2 with a black surface. After that, soak the carbonized sample 2 in deionized water for 72 hours to activate the hydrophilic sites. Finally, place the sample 2 in a 60°C forced air drying oven and dry it for 12 hours to obtain an aluminum-based carbon film photothermal evaporator, which is named C@L-Al-5.
[0054] The present invention uses a concentrated brine drainage mode to assemble an ISE system, which specifically includes filter paper, a beaker polystyrene (PS) foam and the above-mentioned aluminum-based carbon film photothermal evaporator. A small piece of PS foam is used to pad the bottom of a 50ml container and then placed in a 250ml container to form a height difference. Cut two filter paper strips with a size of 2cm×5cm as a water supply channel, and cut two filter paper strips with a size of 0.5cm×8cm as a concentrated brine drainage channel. The head of the water supply channel is placed on the left and right sides of the aluminum-based carbon film photothermal evaporator, and the tail is placed in the simulated seawater, responsible for supplying water to the evaporator material. The head of the concentrated brine drainage channel is placed on the two outer sides opposite to the water supply channel. The heads of the two filter paper strips are close to the evaporator material, responsible for collecting and draining the concentrated brine left after evaporation, and the tail extends into the 250ml beaker for collecting these concentrated brine. The above-mentioned absorber is placed flat on the PS foam. Among them, the area of the PS foam is much larger than the area of the beaker to prevent the incident light source from entering the evaporator system.
[0055] Figure 1 The surface morphology of L-Al and C@L-AL prepared at carbonization temperatures of 500℃, 700℃, and 800℃ was observed using SEM. Figure 1a) is the surface morphology of L-Al. An obvious periodic groove structure is formed under the action of laser etching. Two "pit-like" structures appear during the transverse and longitudinal laser path etching process, one is the superposition of transverse and longitudinal groove structures caused by laser etching, and the other is the exposed Al sheet surface that has not been laser etched. This is because the strong thermal effect causes the Al substrate irradiated by the laser beam to vaporize, melt and cut, and the Al at the edge of the laser beam forms rod-shaped and granular skeletons under the action of thermal effect. These skeletons curl under stress and block the groove structure and the exposed Al sheet surface, resulting in unclear boundaries between the two structures. Under high-power lenses, it can be observed that there are rough surface nanostructures such as velvet and broccoli on the skeleton structure. This rough surface structure can provide capillary force to allow water to diffuse on the grooves and skeletons. The groove and skeleton structures can provide directional flow channels for water transport and ensure the escape of water vapor. As shown in the figure, the groove and skeleton structures can provide directional flow channels for water transport and ensure the escape of water vapor. Figure 1 As shown in Figures bd, after carbonizing furfural, the skeleton structure of L-Al is still retained after high-temperature treatment. In addition, the lateral structure of L-Al was originally flat, but after carbonizing furfural, the uneven drop can be clearly observed. In addition, the lateral and longitudinal etching paths of the laser beam can be clearly observed, and an orderly square array is formed at the intersection of the lateral and longitudinal etching. Each individual square structure is similar to a "swimming pool". The walls around the "swimming pool" are composed of a skeleton structure, and the bottom of the pool is an exposed Al sheet substrate. While the water flow diffuses in the grooves around the square structure, the water climbs up along the skeleton under the action of capillary force. This structure is similar to a salt pan on the seashore, which divides the seawater and is more conducive to evaporation. Under a high-power lens, the rough velvety, broccoli-like and other nanostructures on the surface of L-Al become smooth.
[0056] From the actual samples we prepared, we found that C@L-Al-1 was brown-black, and the furfural prepolymerized on the surface was not well carbonized. The melting point of the Al substrate is low. When carbonized at 800°C, the Al substrate melted and the sample was severely distorted, which is not conducive to the large-scale production and application of C@L-Al-3. Therefore, in subsequent experiments, we chose C@L-Al-2 prepared at 700°C as the light absorber and evaporator of the evaporator.
[0057] Figure 2 The curve of mass loss of the evaporation system changing with time when C@L-Al-2 was used to test the evaporation performance of 3.5 wt%, 10.0 wt% and 15.0 wt% simulated seawater under 1 sun intensity. The results show that as the concentration of the solution increases, its evaporation rate decreases. This is because the increase in solute in the solution leads to an increase in osmotic pressure and tension, making it difficult for water molecules to leave the solution.
[0058] like Figure 3As shown in Figure 2, the desalination rates of C@L-Al-2 for 3.5 wt%, 10.0 wt% and 15.0 wt% simulated seawater were 2.12 kg m -2 h -1 , 1.78 kg m -2 h -1 and 1.69 kg m -2 h -1 , and their energy efficiency is 91.8%, 73.7% and 69.4% respectively. In the traditional water supply mode, salt deposition in the evaporation system starts from the center of the evaporator and spreads to the edge. This indicates that the concentrated brine at the center of the evaporator surface is more likely to reach saturation. Therefore, draining this part of concentrated brine that is easy to reach saturation from the evaporator surface can effectively solve the problem of salt deposition. In order to prove the universality of the evaporator system with concentrated brine drainage mode and the long-term operation stability of C@L-Al-2, the present invention uses C@L-Al-2 to desalinate 3.5wt% simulated seawater for up to 8 hours at 1 sun intensity. Figure 4 The changes in evaporation rate during the process were recorded, and optical photographs of the C@L-Al-2 surface were taken from the beginning to the end of the experiment. The results showed that the evaporation rate during the process was 1.97 kg m -2 h -1 to 2.15 kg m - 2 h -1 The average evaporation rate was 2.09 kg m -2 h -1 This means that C@L-Al-2 can maintain stable and efficient operation during long-term evaporation. Figure 4 There is no salt deposition on the surface of C@L-Al-2, indicating that the use of concentrated brine drainage mode, in which the concentrated high-concentration brine is drained to the recovery device under evaporation, and the low-concentration brine is pumped to the surface of C@L-Al-2 under siphon action, can still achieve excellent salt rejection performance.
[0059] In order to ensure a long service life, 3.5wt% simulated seawater was desalinated for 8 hours every day under 1 sun intensity for 15 days. The evaporation rate change during the process was recorded in Figure 5 During the 15-day test, the maximum average daily evaporation rate was 2.17 kg m -2 h -1 , the minimum value is 1.96 kg m -2 h -1 , with an average evaporation rate of 2.12 kg m -2 h -1The fluctuation of evaporation rate may be caused by fluctuations in humidity, ambient temperature, etc. However, the results of the 15-day test showed that the evaporation rate remained stable and the evaporation performance did not weaken, showing excellent evaporation stability.
[0060] In summary, the present invention improves the structure of the evaporator, improves the photothermal conversion efficiency and evaporation rate of the evaporator, and obtains a high-performance interface solar evaporation system with excellent salt resistance and stable and efficient operation during long-term evaporation by combining the concentrated brine drainage mode. Specifically: L-Al is used as the substrate, and a periodic groove structure is formed on the surface of the Al sheet by laser etching technology. This micro-network structure not only optimizes the distribution of the photothermal conversion material, but also opens up a channel for the effective diffusion of water flow and the rapid escape of steam through the design of the groove structure, and also provides a stable site for the attachment of furfural carbonization. Combined with the excellent photothermal conversion ability of furfural carbon, hydrophilic properties and evaporation enthalpy reduction mechanism, a significant improvement in photothermal conversion efficiency and evaporation rate is achieved; further combined with the concentrated brine drainage mode, a high-performance interface solar evaporation system with excellent salt resistance and stable and efficient operation during long-term evaporation is obtained.
Claims
1. A method for preparing an aluminum-based carbon film photothermal evaporator, characterized in that: The preparation method is as follows: Laser etching is performed on the surface of the Al sheet to obtain an Al sheet with a periodic groove structure on the surface, thereby obtaining product 1; Adding the furfural oxalic acid solution dropwise into the periodic groove-like structure on the surface of the product 1 until a uniform liquid film is formed on the periodic groove-like structure on the surface of the product 1, thereby obtaining the product 2; The product 2 is prepolymerized and carbonized to obtain the product 3; The hydrophilic sites of product 3 were activated to obtain an aluminum-based carbon film photothermal evaporator.
2. The method for preparing an aluminum-based carbon film photothermal evaporator according to claim 1, characterized in that: Laser etching is performed on the surface of an Al sheet to obtain an Al sheet having a periodic groove structure on the surface, and in the step of obtaining product 1, specifically: The laser etching range is 2.5 cm×3.0 cm, the laser spot diameter is 0.05 mm, the laser focal length is 11.0 cm, the spacing between laser beams is 0.1 mm~0.2 mm, the laser beam scanning path is vertical scanning, and the etching path includes horizontal and vertical directions.
3. The method for preparing an aluminum-based carbon film photothermal evaporator according to claim 2, characterized in that: Laser etching is performed on the surface of an Al sheet to obtain an Al sheet having a periodic groove structure on the surface, and in the step of obtaining product 1, specifically: The periodic groove structure is a square array composed of a plurality of square groove structures formed by the intersection of transverse and longitudinal etching paths.
4. The method for preparing an aluminum-based carbon film photothermal evaporator according to claim 1, characterized in that: In the step of adding the furfural oxalic acid solution dropwise to the periodic groove structure on the surface of the product 1 until a uniform liquid film is formed on the periodic groove structure on the surface of the product 1 to obtain the product 2, specifically: The oxalic acid and furfural are mixed in a molar ratio of 0.01 to 0.011 to obtain a furfural oxalic acid solution.
5. The method for preparing an aluminum-based carbon film photothermal evaporator according to claim 1, characterized in that: In the step of prepolymerizing and carbonizing the product 2 to obtain the product 3, specifically: The product 2 was dried at 90 °C for 48 h for prepolymerization.
6. The method for preparing an aluminum-based carbon film photothermal evaporator according to claim 1, characterized in that: In the step of prepolymerizing and carbonizing the product 2 to obtain the product 3, specifically: The prepolymerized product 2 is placed in a protective atmosphere and carbonized at a temperature of 500° C. to 800° C. to obtain a product 3.
7. The method for preparing an aluminum-based carbon film photothermal evaporator according to claim 6, characterized in that: The flow rate under the protective atmosphere does not exceed 50 sccm.
8. An aluminum-based carbon film photothermal evaporator, characterized in that: The method is prepared according to any one of claims 1 to 6.
9. An ISE system, characterized in that: An aluminum-based carbon film photothermal evaporator as described in claim 8 is used as the photothermal absorption layer.
10. An ISE system according to claim 9, characterized in that: Based on the concentrated brine drainage mode, a water supply channel and a concentrated brine drainage channel are set on the aluminum-based carbon film photothermal evaporator, both sides of the aluminum-based carbon film photothermal evaporator are in contact with the head of the water supply channel, and the tail of the water supply channel is in contact with water for supplying water to the aluminum-based carbon film photothermal evaporator; the two opposite outer sides of the water supply channel on the aluminum-based carbon film photothermal evaporator are in contact with the head of the concentrated brine drainage channel, and the tail of the concentrated brine drainage channel is connected to the concentrated brine recovery device.
Citation Information
Patent Citations
Preparation and application of coal tar-based phenolic carbon aerogel
CN115259133A
SiO2 coated PPy / LSDW-Al photo-thermal absorption material and preparation method and application thereof
CN117146451A
High-concentration seawater desalination technology
CN118026327A
Layered porous Janus structure carbon-graphene aerogel and preparation method thereof
CN118771363A